Software Development Methodologies (2000–2026): A Scopus-Based Bibliometric Mapping of Scholarly Output and Thematic Evolution - Judijanto, Loso (West Science Information System and Technology, 2026)
In this study, an analysis will be conducted on the intellectual structure and thematic development of the literature concerning software development methodologies during the time frame of 2000 to 2026 through the bibliometric method. The data were retrieved from the Scopus database and analyzed using VOSviewer to create various visualization networks, including co-authorship, citations, and keyword co-occurrences. According to the findings, there was a substantial increase in the amount of literature produced within the study domain, demonstrating the rising significance of software development methodologies in both theoretical and practical fields. Through the co-authorship analysis, it was observed that research collaboration tends to occur mainly between several dominant countries and organizations, but possibilities for collaboration across the globe still exist. In terms of citation analysis, the most cited sources were mostly related to the creation of software development tools, which highlighted the applicability of the domain. In addition, through the keyword co-occurrence and overlay analysis, the thematic development of the literature shifted from classic software engineering techniques to adaptable and smart methods, including agile development, artificial intelligence, and machine learning. Moreover, other emerging themes, such as sustainability, indicated the wide range of applications for the study field.